Ответы и объяснения

  • Участник Знаний
2014-03-07T17:14:20+00:00
√(8-√63)*√(8-√63)/√(8+√63)√(8-√63) + √63 +2007=(√(8-√63))²/(8-√63) + √63  +2007=
(8-√63)/(8-√63)+ √63  +2007=1++ √63  +2007=2008+√63
Так нельзя решать
Здесь можно только Корень(A/B)+корень С=Корень(корень A/B+Корень C)^2=Корень( (Корень A/B)^2+2 корень A/B*Корень С+(Корень С)^2=Корень(A/B+2 корень A/B*КореньС+ C)
2014-03-07T17:24:28+00:00
Корень((8- корень 63)/(8 +корень 63))+ корень 63+2007=Корень(Корень((8- корень 63)/(8 +корень 63))+ корень 63)^2 +2007=Корень(((8- корень 63)/(8 +корень 63))^2+2 корень(8- корень 63)*корень 63/корень(8 +корень 63) +63) +2007;под общую дробь первые два числа 
Корень(((8- корень 63)/(8 +корень 63))+2 корень(8- корень 63)*корень 63*корень(8 +корень 63)/(8 +корень 63) +63) +2007=Корень(((8- корень 63)/(8 +корень 63))+2 корень(64-63)*корень 63/(8 +корень 63)+63)+2007=Корень((8+корень 63)/(8 +корень 63)+63)+2007=8+2007=2015